World Economic Outlook, October 2008 : Financial Stress, Downturns, and Recoveries. (World Economic Outlook; World Economic Outlook ;, 2008)
A unique international exercise in information-gathering and analysis An extraordinary confluence of global forces has kept the world economy strong in the past few years, but there are now numerous challenges to growth. The World Economic Outlook (WEO) presents the IMF's leading economists' analyses of global economic developments during the near and medium terms. It is a respected, one-stop, trusted resource offering remarkable insight, balance, and perspective to decision makers and policymakers worldwide. Published at least twice yearly, the World Economic Outlook presents the outlook for growth, inflation, trade, and other economic developments in a clear, practical format. Each WEO considers the issues affecting advanced and emerging economies. The analytic chapters provide the global intelligence required to deal with global interdependence. These analyses focus on pressing concerns or hotly debated issues, putting prospects for liquidity, inflation, and growth into context. The statistical appendix presents historical data as well as projections and selected series from World Economic Outlook database updated for each report. The October 2008 edition examines commodity prices and inflation, economic cycles in the aftermath of financial crises, the role of fiscal policy during downturns, and current account imbalances in emerging economies. Recent analytic chapters have examined climate change, the housing cycle, commodity prices, capital inflows, globalization and inequality, and the global business cycle.